2011
DOI: 10.1111/j.1447-0594.2011.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnosis in the elderly referred to a consultation‐liaison psychiatry service in a general geriatric hospital in Japan

Abstract: The referring doctors in this survey had an insufficient level of diagnostic accuracy for psychiatric disorders. Delirium and psychoactive substance-use disorders were often misdiagnosed as depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…The studies from other parts of the world also suggest that the concordance rates of diagnosis made by CL psychiatry team, and the physician/surgeons are low for various ICD-10 categories. [19] These findings possibly reflect the diagnostic inaccuracy/misdiagnosis in the hand of the physician/surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies from other parts of the world also suggest that the concordance rates of diagnosis made by CL psychiatry team, and the physician/surgeons are low for various ICD-10 categories. [19] These findings possibly reflect the diagnostic inaccuracy/misdiagnosis in the hand of the physician/surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[181920] These studies have reported 41.5%–47.4% concordance between the physician/surgeons diagnosis and the diagnosis made by the psychiatrist. [1820] A study from Japan, which evaluated the concordance of diagnosis between physician/surgeons and psychiatrists for elderly referred to CL psychiatry services reported kappa statistics of 0.47 for F0 category, 0.27 for F1 category, 0.28 for F2/3 category, and F 0.32 for F4/5 category.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,34-36 Although these studies do not adequately account for possible comorbidity and include many complex diagnostic challenges, equally,referrals to psychiatric consultation liaison services represent a small proportion of cases of delirium that occur in hospital settings and the full extent of misdiagnosis is likely to be considerably greater than that described in these studies.…”
Section: Assessment In Clinical Practicementioning
confidence: 97%
“…Fear of medico-legal consequences and referrer’s anxiety suggested as reasons for referral rates.Cepoiu et al 2008 [42]N/A36 articles (comprising of 50935 inpatients)Meta-analysis of recognition of depression in inpatients by non-psychiatric doctorsSensitivity was found to be 36.4 % and specificity was 83.7 %Clarke et al 1995 [43]Australia, Melbourne, Monash Medical Centre987 medical and surgical patientsProspective patient review, comparing diagnosis of depression made by psychiatrists and non-psychiatristsDiagnostic concordance of depression 74 %, 41 % false positive rate and 15 % false negative rate.Dilts et al 2003 [44]UK, York Hospital346 medical inpatient consultationsRetrospective review comparing initial impression of primary medical providers to final psychiatric diagnosisInitial diagnosis of cognitive disorders and substance use disorder is likely to be correct. Initial diagnosis of depression is wrong in half the cases.Judd et al 1997 [45]Australia, Melbourne392 HIV/AIDS patients referred for CLPRetrospective chart reviewDiagnostic concordance of depression was 79 %, 20 % false positive rate and 23 % false negative rateRyan et al 1995 [46]UK, Castle Hill Hospital50 geriatric inpatientsProspective cohort study examining agreement between psychiatrist and geriatricians on depression and dementiaSome evidence suggesting lower recognition of depression by geriatricians.Yamada et al 2012 [47]Japan, Tokyo Metropolitan Geriatric Hospital172 geriatric inpatientsProspective diagnostic review of CLP consultationsAlmost half of patients with depression diagnosed by referrers were found to be delirium.Boland et al 1996 [48]US, teaching hospital4396 inpatients referred for consultationsRetrospective chart review40 % of patients initially identified by referrer to be depressed were found not to be depressed by psychiatry consultantsCanuto et al 2015 [49]Switzerland, University hospital of Geneva148 inpatients over age of 60Prospective cohort study40 % of patients initially referred for depression were diagnosed with depression by CLP.Smith et al 1995 [50]Australia, Melbourne, Monash Medical Centre2347 inpatient referralsRetrospective chart review56 % of patients suspected by psychiatrist for substance use disorder were missed by referrers.Su et al 2011 [51]Taiwan, region general hospital1007 inpatient referralsRetrospective chart reviewOnly 41.5 % of initial physician’s impression matches with psychiatrist’s fin...…”
Section: Appendixmentioning
confidence: 99%